2002
DOI: 10.1046/j.1365-8711.2002.05189.x
|View full text |Cite
|
Sign up to set email alerts
|

The quiescent light curve and the evolutionary state of GRO J1655-40

Abstract: We present ellipsoidal light‐curve fits to the quiescent B, V, R and I light curves of GRO J1655–40 (Nova Scorpii 1994). The fits are based on a simple model consisting of a Roche‐lobe‐filling secondary and an accretion disc around the black hole primary. Unlike previous studies, no assumptions are made concerning the interstellar extinction or the distance to the source; instead these are determined self‐consistently from the observed light curves. In order to obtain tighter limits on the model parameters, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
148
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(171 citation statements)
references
References 38 publications
22
148
1
Order By: Relevance
“…Adopting the distance of 3.2 kpc by Hjellming & Rupen (1995), and an average reddening law (R V = 3.2), they obtain E(B − V) = 1.25 ± 0.17 in agreement with previous publications. Beer & Podsiadlowski (2002) reanalyzed the lightcurve in quiescence obtained by Orosz & Bailyn (1997). In their models, the distance is said to be a free parameter, although it is not clear if this parameter has been allowed to go as low as 1.0 kpc.…”
Section: The Problem Of the Distancementioning
confidence: 99%
“…Adopting the distance of 3.2 kpc by Hjellming & Rupen (1995), and an average reddening law (R V = 3.2), they obtain E(B − V) = 1.25 ± 0.17 in agreement with previous publications. Beer & Podsiadlowski (2002) reanalyzed the lightcurve in quiescence obtained by Orosz & Bailyn (1997). In their models, the distance is said to be a free parameter, although it is not clear if this parameter has been allowed to go as low as 1.0 kpc.…”
Section: The Problem Of the Distancementioning
confidence: 99%
“…Using the same arguments as in the case of XTE J1819-254, we reset this lower limit to -75 km s 1 . For XTE J1550-564, XTE J1819-254 and 4U 1543-47, we keep original Repetto et al (2012) estimates, but we mark our modest revisions both in Table 7 ) adopted from Beer & Podsiadlowski (2002). We chose this model as this mass was later confirmed by X-ray timing analysis (Motta et al 2014;   M 5.31 0.07…”
mentioning
confidence: 99%
“…This makes it quite difficult for a significant mass fraction of iron to have escaped from the collapsing matter in the SN event because iron is formed in the inner layers of the star. Israelian et al (1999) found in Nova Scorpii 94 that while -elements were enhanced Fe was not, in spite of the lower mass of the compact object (5:4 AE 0:3 M ; Beer & Podsiadlowski 2002) than that in A0620À00. Thus, the SN may not eject any iron, and it therefore seems quite plausible that the slightly higher than solar Fe abundance of the secondary star in A0620À00 reflects its primordial value.…”
Section: Evv Olutionary Scenariomentioning
confidence: 95%